Isolation and identification of pandemic influenza virus H1N1/2009 S-OIV from commercial and backyard swine in Costa Rica - León, Bernal (2014)
Influenza viruses are a threat not only to international trade of animal products but also to human health. The isolate H1N1/2009 S-OIV was diagnosed in mid-2009 in Mexico and the United States of America as a new variant of influenza in humans, and then was declared a pandemic by the World Health Organization (WHO). Costa Rica was the fourth country in the Americas to demonstrate the presence of this swine variant in humans. In 2010, the Food and Agriculture Organization of the United Nations (FAO) encouraged public awareness in some American countries like Costa Rica, where FAO sponsored and organized a program for detection and characterization of influenza H1N1 in pigs. To ascertain whether H1/N1/2009 S-OIV was present or not in Costa Rican swine herds, a distributed sampling of 509 pigs from 25 farms was conducted from across all of the Costa Rican provinces. The results confirmed the presence of this subtype in at least 2 of the sampled farms. In one case, nasal swabs from 11 pigs tested positive in Real-time PCR (RRT-PCR) and were confirmed using virus isolation. The second case was found positive by RRT-PCR but was not confirmed by virus isolation.  Phylogenetic studies based on HA, NA and M genes showed that this variant is closely related to previously reported H1N1/2009-S-OIV worldwide sequences from human origin. This finding should be brought to the attention of local and global human and animal health agencies (e.g. WHO, OIE). This report also shows the usefulness of conducting surveillance on farms where poultry, wild birds, pigs and humans interact, in order to improve early detection and prevent the spread of possible new variants that can become pandemic strains.